Half the world away : a qualitative study exploring migration and motherhood in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Ni Bhroin, Riona (Massey University, 2012)
Migration is a global phenomenon. An estimated 214 million people worldwide have migrated from their countries of origin; 49% of whom are women. Previous research suggests that the juxtaposition of migration and motherhood has a considerable impact on the identity of women, and is associated with social isolation, economic strain and mental health concerns. In New Zealand, 23% of the population of women were born outside the country; despite this, there is limited local research into the impact of migration and motherhood. Half the World Away is a contribution to this gap in psychological research; the project explores the lived experience of migrant mothers in New Zealand. Feminist methodologies guide this research. Stories of migration and motherhood are explored using narrative analysis against the backdrop of La Mestiza metaphor. Half the World Away rejects previous assertions that migrant women become marginal women due to our inability to reconcile psychological conflict caused by migration. It explores how cultural discourses and master narratives split us into (n)either/(n)or and how women negotiate migration and motherhood by adopting pluralistic identities that transcend the conflicting realities of living between two cultures. Half the World Away offers a holistic analysis of experience and challenges dichotomous, linear models of the same by exploring the fluidity of migrant identity against socio-cultural and political spaces. This research offers new knowledge regarding identity, social and economic features of the lived experience of migrant women and mothers in New Zealand, thereby providing a new cultural resource to inform and guide psychological practice.
Keywords: Women immigrants; Motherhood; New Zealand